Risk factors associated with overweight and obesity in HIV-infected people: Aging, behavioral factors but not cART in a cross-sectional study. Issue 23 (June 2018) - Obry-Roguet, Véronique; Brégigeon, Sylvie; Cano, Carla E.; Lions, Caroline; Zaegel-Faucher, Olivia; Laroche, Hélène; Galie, Sébastien; De Lamarlière, Perrine Geneau; Orticoni, Matthieu; Soavi, Marie-Josèphe; Saout, Armelle; Poizot-Martin, Isabelle
Abstract : Abstract: Identifying risk factors associated with overweight and obesity in HIV-infected patients. A cross-sectional study analyzing data from patients attending an HIV outpatient unit. Overweight was defined as body mass index (BMI) ≥25 kg/m 2 ; <30 kg/m 2, obesity was ≥30 kg/m 2 . Patients' characteristics contemporary to BMI assessment were collected. Multivariate logistic regression identified risk factors associated with overweight/obesity. Eight hundred sixty-two patients, median age 51 years, 21.5 years of HIV infection follow-up, 585 (68%) male, 829 (96%) receiving combined antiretroviral therapy (cART) for median 16.7 years, 768 (91%) HIV load <40 copies/mL, 618 (73%) CD4 + ≥500 cells/mm 3 ; 266 (31%) HCV + serology, 110 (13%) had detectable HCV-RNA. Overweight affected 191 (22%) patients and obesity 46 (5%). Overweight and obesity were associated with age, HIV follow-up duration, and HIV transmission risk group. Overweight was also associated with gender and HCV status. In patients with substance use data, overweight was associated with alcohol and nonsmoking status. Obesity was associated with nonsmoking and ex-smoker status. Overweight/obesity were not found associated with cART or immune cell counts. In HIV-infected people, aging, alcohol consumption, nonsmoking, and ex-smoker status, the absence of HCV coinfection and to have cleared HCV infection are associated with overweight and/or obesity. Clinicians should be aware of these trends and consider introducing weight management programs as part of routine HIV care.